Peningkatan Kompetensi Siswa SMKN 1 Kramatwatu dalam hal comunication, critical thingking, collaboration dan creative pada kegiatan Kihajar STEM Tingkat Nasional 2023 - Alamsyah Alamsyah; Apriliano Chandra Diva; Irwan Syah; Alif Kautsar; Mustofa Abi Hamid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The author provides training and guidance aimed at improving student competence in terms of communication, creative thinking, collaboration and creativity at the 2023 national level Ki Hajar STEM activities. This research uses quantitative research methods with a quasi-experimental type. There are two stages in this research, the preparation stage, namely the preparation stage before the competition and the implementation stage, namely the stage of participating in the Kihajar STEM competition activities. The innovation they created, namely a cellphone device or automatic sprinkler based on solar cells, increased their abilities in terms of creativity and were able to work together in making this cellphone device which was used as a tool to compete in the Kihajar STEM competition. 4C competencies consist of critical thinking competencies, creativity competencies, communication competencies and collaborative competencies.